ANALISIS KEBUTUHAN BELAJAR UNTUK MENYUSUN PERANGKAT PEMBELAJARAN BIPA TINGKAT PEMULA YANG BERORIENTASI AMERICAN COUNCIL FOR TEACHING FOREIGN LANGUAGE (ACTFL) - Azza Aulia Ramadhani (IKIP Budi Utomo Malang, 2017)
This study aims to obtain an objective description of the results of learniing needs analysis for BIPA’s learners at beginner level to arrange learning tools. This research uses qualitative design with descriptive approach. The data of this research are words and documents which are then analyzed. Based on the results of the analysis obtained conclusions, namely the results of learning needs analysis BIPA’s students at beginner level.